The impact of endogenous annexin A1 on glucocorticoid control of in ammatory arthritis - Patel, Hetal B.; Kornerup, Kristin N.; Sampaio, Andre L. F.; Acquisto, Fulvio D.; Seed, Michael P.; Girol, Ana Paula [UNESP]; Gray, Mohini; Pitzalis, Costantino; Oliani, Sonia M. [UNESP]; Perretti, Mauro (B M J Publishing Group, 2012)
Objectives To establish the role and effect of glucocorticoids and the endogenous annexin A1 (AnxA1) pathway in inflammatory arthritis.Methods Ankle joint mRNA and protein expression of AnxA1 and its receptors were analysed in naive and arthritic mice by real-time PCR and immunohistochemistry. Inflammatory arthritis was induced with the K/BxN arthritogenic serum in AnxA1(+/+) and AnxA1(-/-) mice; in some experiments, animals were treated with dexamethasone (Dex) or with human recombinant AnxA1 or a protease-resistant mutant (termed SuperAnxA1). Readouts were arthritic score, disease incidence, paw oedema and histopathology, together with pro-inflammatory gene expression.Results All elements of the AnxA1 pathway could be detected in naive joints, with augmentation during ongoing disease, due to the infiltration of immune cells. No difference in arthritis intensity of profile could be observed between AnxA1(+/+) and AnxA1(-/-) mice. Treatment of mice with Dex (10 mu g intraperitoneally daily from day 2) afforded potent antiarthritic effects highly attenuated in the knockouts: macroscopic changes were mirrored by histopathological findings and pro-inflammatory gene (eg, Nos2) expression. Presence of proteinase 3 mRNA in the arthritic joints led the authors to test AnxA1 and the mutant SuperAnxA1 (1 mu g intraperitoneally daily in both cases from day 2), with the latter one being able to accelerate the resolving phase of the disease.Conclusion AnxA1 is an endogenous determinant for the therapeutic efficacy of Dex in inflammatory arthritis. Such an effect can be partially mimicked by application of SuperAnxA1 which may represent the starting point for novel antiarthritic therapeutic strategies.